Active packaging films with natural antioxidants to be used in meat industry: A review. (November 2018) - Domínguez, Rubén; Barba, Francisco J.; Gómez, Belén; Putnik, Predrag; Bursać Kovačević, Danijela; Pateiro, Mirian; Santos, Eva M.; Lorenzo, Jose M.
Abstract: Spoilage of meat products during processing, distribution and exposure in the markets have an important negative impact on meat industry from an economic point of view. Two of the main problems of meat and products during processing and subsequent storage are lipid oxidation and deterioration due to microorganism growth. In this context, several packaging alternatives have been developed by meat industry in order to limit these losses and to extend the meat products´ shelf life. Over the last years, the use of active packaging has been proposed as an alternative to traditional packaging. The principle of active packaging, particularly antioxidant active packaging, consists of including active agents in the packaging which interact with meat and/or its environment, either by trapping pro-oxidant compounds or by releasing antioxidant compounds in order to delay degradation due to lipid oxidation. Therefore, the use of active packaging is presented as a future option to solve the problems derived from oxidative deterioration of meat and meat products. However, its use will depend on the costs involved in the development of this active packaging. Therefore, this review will give an overview about the use of active packaging and natural antioxidants, the active film development techniques, as well as the use of biopolymers as substitutes for synthetic polymers and their direct application in the meat industry. Graphical abstract: Highlights: Antioxidant films show a great effectiveness to protect the meat against oxidation. Bioactive compounds from natural sources have a great antioxidant power. Biopolymers have many advantages and could reduce the use of synthetic polymers. The development of antioxidant films must be scaled to the industry to boost its use.